IMPLEMENTASI MOODLE SEBAGAI MEDIA PEMBELAJARAN JARAK JAUH - Indah Nopita Sari; Annisa Prima Exacta (UNIVERSITAS TANJUNGPURA, 2021)
This study aims to determine the results of implementing the Moodle application as a distance learning medium for students who cannot do face-to-face learning, due to the COVID-19 pandemic. This type of research is a qualitative descriptive with a frequency distribution, which is concluded based on the data obtained during the study. The sample studied was 21 students. The results of the study found that there were 16.9% of students answered strongly agree; 45.5% of students answered agree; 30.7% of students answered disagree; 6.9% of students answered strongly disagree. Some students who answered disagreed or strongly disagreed had problems, namely not having a cellphone/laptop, unstable internet network, and expensive data packages. Educators must carefully prepare the material to be delivered and students must look for a stable network location. In conclusion, using Moodle as a distance learning medium is very effective, to support learning activities that cannot be carried out during the COVID-19 pandemic. The availability of infrastructure is very necessary so that learning objectives can be realized.